DIVERSITY OF CORAL REEF AND ITS IMPACT ON THE AVAILABILITY OF ANGEL FISH (POMACANTHUS SP.) PRODUCTION IN THE SPERMONDE PANGKAJENE AND KEPULAUAN WATERS, SOUTH SULAWESI - Kasmi, Mauli (Journal of Agriculture, 2023)
The objective of this research was to estimate and analyze the availability of Angel fish (Pomacanthus sp.) based on the coral diversity conditions in the Spermonde waters of Pangkep Regency, South Sulawesi. The research method was based on parallel sampling of fish abundance (visual census) and coral cover percentage (Point Intercept Transect) at the study sites, namely Liukang Tumppabiring and Liukang Tangaya waters. The results showed that Liukang Tuppabiring had a fish abundance of 0.00005 individuals per square meter with a standing stock of 138 individuals, while Liukang Tangaya had a fish abundance of 0.005 individuals per square meter with a standing stock of 35,121 individuals. The abundance of Angel fish did not correlate positively with live coral cover, but its presence was influenced by the structural growth forms of the coral, namely branching, submassive, and massive coral in crevices. The production status of Angel fish in the Spermonde waters has exceeded the maximum sustainable yield (MSY). Therefore, additional fishing efforts would decrease the production of Angel fish. This indicates that the Angel fish has been overfished, which can affect its supply. In addition, the inverted curved supply curve indicates a decreasing supply, even with increasing fish prices, as it is suspected that the stock is decreasing.